Highly labeled methylene blue-ds DNA silica nanoparticles for signal enhancement of immunoassays: application to the sensitive detection of bacteria in human platelet concentrates. Issue 10 (24th April 2018) - Bonnet, Romaric; Farre, Carole; Valera, Lionel; Vossier, Ludivine; Léon, Fanny; Dagland, Typhaine; Pouzet, Agnès; Jaffrézic-Renault, Nicole; Fareh, Jeannette; Fournier-Wirth, Chantal; Chaix, Carole
Abstract : A nanoparticle-based electrochemical immunoassay for bacteria detection in platelet concentrates. Abstract : A nanoparticle-based electrochemical sandwich immunoassay was developed for bacteria detection in platelet concentrates. For the assay, magnetic beads were functionalized with antibodies to allow the specific capture of bacteria from the complex matrix, and innovative methylene blue-DNA/nanoparticle assemblies provided the electrochemical response for amplified detection. This nanoparticular system was designed as a temperature-sensitive nano-tool for electrochemical detection. First, oligonucleotide-functionalized nanoparticles were obtained by direct synthesis of the DNA strands on the nanoparticle surface using an automated oligonucleotide synthesizer. Densely packed DNA coverage was thus obtained. Then, DNA duplexes were constructed on the NP surface with a complementary strand bearing a 3 methylene blue tag. This strategy ultimately produced highly functionalized nanoparticles with electrochemical markers. These assemblies enabled amplification of the electrochemical signal, resulting in a very good sensitivity. A proof-of-concept was carried out for E. coli detection in human platelet concentrates. Bacterial contamination of this complex biological matrix is the highest residual infectious risk in blood transfusion. The development of a rapid assay that could reach 10–10 2 CFU mL −1 sensitivity is a great challenge. The nanoparticle-based electrochemical sandwich immunoassay carried out on a boron doped diamond electrode proved to be sensitive for E. coli detection in human platelets. Two antibody pairs were used to develop either a generic assay against certain Gram negative strains or a specific assay for E. coli . The methylene blue-DNA/nanoparticles amplify sensitivity ×1000 compared with the assay run without NPs for electrochemical detection. A limit of detection of 10 CFU mL −1 in a biological matrix was achieved for E. coli using the highly specific antibody pair.